Trade unions in a civilized market economy - Walther Müller-Jentsch (Management Revue, 2012)
The article tries to answer an old question of economic theory and institutional economics: How do trade unions fit into a market economy? Are they a constitutive element of the market order or: are they a source of irritation and disruption?
Keywords: J51; J53; J83; 650; trade unions; economic theory; market economy; labour market; collective bargaining; Germany